The Emperor’s New Clothes or problems with interregnum? Dynamic capabilities – review of concepts - Gorgól, Jolanta (Management Sciences, 2017)
The aim of the article is to address the problems of the Dynamic Capabilities Approach (DCV) with regard to polarisation, inconsistencies and tautologies, and to propose a new linguistic solution for the challenges of DCV. Through adopting the definitions of the general terms used in DCV (like capacity, ability and capability) from the English language dictionaries, the author builds the concept of capability activation and organizational dynamics. The linguistic platform presented in the article allows to link different perspectives of publications discussing DC issues. By drawing up a new perspective on the concept of capabilities and organizational dynamism, the article clears the problems with tautologies. When it comes to contribution, this article is the first publication from a series of papers extensively discussing the strategic competitive advantage of organization in the perspective of author’s Concept of Organizational Competence Emergence (CEC)
Nauki o Zarządzaniu = Management Sciences, 2017, Nr 1 (30), s. 4-15
Keywords: dynamic capabilities; capability activation; dynamism of organization; linguistic platform; Competence Emergence Concept; zdolności dynamiczne; aktywacja zdolności; potencjał organizacji; dynamizm organizacji; platforma językowa; koncepcjapowstawania kompetencji